Juridical Analysis Of The Role Of The Wage Board In Determining The Minimum Wage In Batam City - Hendri Hendri; Fadlan Fadlan; Lagat Parroha Patar Siadari; Erniyanti Erniyanti (Journal of Innovative and Creativity, 2025)
The determination of minimum wage is one of the instruments of state policy to realise social justice for workers, especially in guaranteeing a decent income and protecting weak economic groups. The Wage Council, as a tripartite institution consisting of elements of government, employers, and labour unions, has a strategic role in formulating minimum wage recommendations to regional heads. This research is motivated by the reality that although legal arrangements on the role of the Wage Council have been regulated in various regulations, the implementation in the field, especially in Batam City, has not fully reflected the principles of social justice as referred to in Articles 27 and 28D of the 1945 Constitution. This research aims to juridically analyze the role and function of Wage Council in the process of determining minimum wage for workers in Batam City, assess the obstacles faced, and provide solutions based on the theoretical approach of justice, legal system, and legal certainty. The research methods used are normative juridical and empirical juridical, with primary data obtained through interviews with government elements, trade unions, and employers, as well as secondary data in the form of legislation and legal literature. The results show that normatively the role of the Wage Board has a clear legal basis, but in its implementation there are still obstacles such as imbalance in bargaining position, political intervention, and weak supervision of the application of wage structures and scales. Solutions offered include strengthening regulations based on legal certainty, increasing the technical capacity of Council members, and participatory strategies that involve workers more actively. The research recommends institutional reform and strengthening transparency to ensure a fairer and more sustainable wage system.